Perhitungan dan Pencatatan Pajak PPH Pasal 23 Terhadap Sewa Pada PT. Recon Sarana Utama Tahun 2024 - Atika Nur Cahyo Pratiwi; Nur Fitri Dewi (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to analyze the implementation of the calculation and recording of Income Tax (PPh) Article 23 on rental transactions at PT. Recon Sarana Utama. The research employs a descriptive qualitative method, using primary data obtained through interviews and observations, as well as secondary data from company documents and relevant regulations, particularly Law No. 36 of 2008 on Income Tax. The findings indicate that the calculation of PPh Article 23 at PT. Recon Sarana Utama has been carried out in accordance with the legal provisions, although misunderstandings still occur with several vendors regarding tax withholding. These misunderstandings arise due to vendors’ limited understanding of the provisions of PPh Article 23 and ineffective communication between the parties. As a corrective measure, PT. Recon Sarana Utama conducts reconciliations with vendors to clarify tax regulations and align understanding related to the calculation and recording of PPh Article 23. This study highlights the importance of communication and education in tax management within business practices.